Réponses

  • Cetb
  • Modérateur confirmé
2012-06-04T18:42:57+02:00

a) 

|2(x-y)=16

|3x+2(y-3)=6y-37

Procédons par substitution

 

|2x-2y=16

|3x+2(y-3)=6y-37

 

|2x=16+2y

|3x+2(y-3)=6y-37

 

|x=8+y

|3x+2(y-3)=6y-37

 

|x=8+y

|3(8+y)+2(y-3)=6y-37

 

|x=8+y

|24+3y+2y-6=6y-37

 

|x=8+y

|18+5y=6y-37

 

|x=8+y

|y=18+37=55

 

|x=8+55=63

|y=55

 

 

b)

|3(x-y)=13-y 

|3(y+x)=2x+9

 

|3x-3y=13-y 

|3y+3x=2x+9

 

Procédons par substitution

 

|3x=13+2y 

|3y+3x=2x+9

 

|(3x-13)/2=y 

|3y+3x=2x+9

 

|(3x-13)/2=y 

|3(3x-13)/2+3x=2x+9

 

|(3x-13)/2=y 

|(9x-39)/2=9-x

 

|(3x-13)/2=y 

|(9x-39)=18-2x

 

|(3x-13)/2=y 

|11x=57

 

|(3x-13)/2=y 

|x=57/11

 

|(3*(57/11)-13)/2=y 

|x=57/11

 

|(171/11)-13)/2=y 

|x=57/11

 

|171/11-143/11)/2=y 

|x=57/11

 

|(28/11)/2=y 

|x=57/11

 

|y=14/11 

|x=57/11